2020
DOI: 10.3390/molecules25194481
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lactobacillus plantarum subsp. plantarum with Potential Probiotic Activities for Inhibiting ETEC K88 in Weaned Piglets

Abstract: For screening excellent lactic acid bacteria (LAB) strains to inhibit enterotoxigenic Escherichia coli (ETEC) K88, inhibitory activities of more than 1100 LAB strains isolated from different materials, and kept in the lab, were evaluated in this study. Nine strains with inhibition zones, at least 22.00 mm (including that of a hole puncher, 10.00 mm), and good physiological and biochemical characteristics identified by 16S DNA gene sequencing and recA gene multiple detection, were assigned to Lactobacillus (L.)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Enterotoxigenic E. coli (ETEC) K88 is one of the most common pathogens causing diarrhea in postweaning piglets. After colonizing the small intestine, ETEC produces enterotoxins that stimulate intestinal inflammation, thereby causing diarrhea ( 4 ). Piglets can no longer obtain passive immunity from sows after weaning, which raises their susceptibility to ETEC infections.…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…Enterotoxigenic E. coli (ETEC) K88 is one of the most common pathogens causing diarrhea in postweaning piglets. After colonizing the small intestine, ETEC produces enterotoxins that stimulate intestinal inflammation, thereby causing diarrhea ( 4 ). Piglets can no longer obtain passive immunity from sows after weaning, which raises their susceptibility to ETEC infections.…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…Pazhoohan et al [33] reported that Lactobacillus showed antagonistic activity against ETEC with an inhibition zone diameter of 27.00 mm by the same method. Wang et al [20] screened the strain L. plantarum subsp. plantarum ZA3, which showed antagonistic activity against ETEC K88 with an inhibition zone 23.00 mm in diameter by this method.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion ability of selected LAB strains is reflected by cell surface hydrophobicity and auto-aggregation, and these two characteristics were tested using methods described by Wang et al [20]. Strains with high cell surface hydrophobicity and auto-aggregation were selected for 16S rRNA gene analysis.…”
Section: Cell Surface Hydrophobicity and Auto-aggregation Of Selected Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang W et al [17]. Simulated gastric uid: 0.35 g of pepsin was diluted in 100 mL 0.2% saline, pH was adjusted to 2.5 with dilute hydrochloric acid, ltered and sterilized.…”
Section: Resistance To Simulated Gastrointestinal Tract (Git) Conditionsmentioning
confidence: 99%